The relationship between student interest and discipline in compulsory school morning exercise programs: a cross-sectional correlational study in an indonesian vocational school - Era Oktavia; Eval Edmizal; Tjung Hauw Sin; Anisa Sholiha Mia (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
Regular participation in physical activity is essential for adolescents' physical and psychological well-being. However, students often demonstrate varying levels of participation in school-based physical education programs due to differences in motivation and personal interest. This study examined the relationship between student interest and discipline in participating in the Senam PAHAMI morning exercise program at SMKN 4 Padang, Indonesia. Drawing on Self-Determination Theory and Expectancy-Value Theory, the study hypothesized that higher levels of student interest would be associated with greater discipline. A quantitative correlational research design was employed involving 427 Grade X and XI students, representing the entire eligible population through a census approach. Data were collected using Likert-scale questionnaires measuring student interest and discipline. The instruments demonstrated good internal consistency, with Cronbach's alpha coefficients of 0.82 and 0.85, respectively. Data were analyzed using the Kolmogorov–Smirnov normality test, Pearson product-moment correlation, and the coefficient of determination. The findings indicated moderately high levels of both interest (M = 57.70, SD = 4.62) and discipline (M = 69.33, SD = 5.49). A statistically significant positive correlation was found between student interest and discipline (r = 0.413, p < 0.001). The coefficient of determination showed that student interest explained 17.02% of the variance in discipline, while the remaining variance may be attributed to factors such as teacher supervision, school culture, peer influence, and individual characteristics. These findings support Self-Determination Theory and Expectancy-Value Theory, emphasizing that fostering students' intrinsic interest can enhance discipline in school physical activity programs. The results provide practical implications for physical education teachers and school administrators in promoting student engagement and participation.